Experimental Assessment of a Magnetic Induction-Based Receiver for Magnetic Communication - Jang-Yeol Kim; Hyun Joon Lee; Jae-Ho Lee; Jung Hoon Oh; In-Kui Cho (IEEE Access, 2022)
This paper presents the topology of a novel approach to magnetic communication using a differential magnetic induction (MI)-based receiver and a differential MI receiving sensor. In this paper, a differential MI sensor based on two ferromagnetic cores is proposed as a receiving sensor, unlike the air coil-type MI sensor in the conventional search coil sensor concept. This differential MI sensor has the advantages of ultra-high sensitivity characteristics of the pT/ $\surd $ Hz level, which can detect weak magnetic fields in magnetic communication; moreover, the sensor is smaller than a conventional air coil MI sensor. The proposed differential MI sensor contributes to improving sensor performance by increasing its signal-to-noise ratio. The design and fabrication of the proposed MI sensor were based on a printed circuit board (PCB). The pickup coil of the PCB-based MI sensor directly wound the pickup coil onto a ferromagnetic core composed of Ni-Zn ferrite material. To analyze the key factors that affected the performance of the receiver, the magnetic field-to-voltage conversion ratio (MVCR) and equivalent magnetic spectral density measurements of the proposed PCB-based MI sensor were performed. Wireless digital communication using quadrature phase shift keying (QPSK), which is less sensitive to noise and has a high data rate, was used to evaluate the proposed MI-based receiver. The transmitted and received waveforms were compared to confirm that the transmitted digital data were accurately received as a result of the final demodulation of the receiver. Additionally, several performance metrics, such as constellation and error vector magnitude, were measured. The results of the comprehensive analysis confirmed the applicability of the proposed differential MI-based receiver to a magnetic field.